DAKWAH MELALUI JALUR PENDIDIKAN: (Studi Terhadap Dakwah M. Natsir Melalui Jalur Pendidikan) - Lukman Ma'sa (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2025)
Da'wah and education are two aspects that are closely related and inseparable, like two sides of a coin. Essentially, da'wah is an educational process that aims to direct humans towards self-improvement. Thus, an educator also has a position as a da'i who carries out Allah's mandate in calling for goodness and preventing evil. This is what this study is trying to study. This study uses qualitative research methods with the types of library research approaches and historical approaches. The results of this study show that M. Natsir succeeded in doing da'wah through the educational path very well. His contribution to the spread of Islamic teachings through education has had a wide impact and was felt by many parties, including; Natsir's concept of integral education has inspired many people in organizing Islamic education in Indonesia, and initiated the establishment of Islamic campuses in Indonesia.